The future of state-owned financial institutions - Caprio, Gerard; NetLibrary, Inc. (Washington, D.C. : Brookings Institution Press, 2004)
"Focuses on the rationale and performance of state-owned financial i nstitutions in emerging markets, as well as on possible government poli cies for either privatizing or managing them"--Provided by publisher.
The transformation of state-owned banks / James A. Hanson -- Observa tions from an International Monetary Fund survey / David Marston and Ad itya Narain -- Fiscal transparency and state-owned banks / Manal Fouad ... [et al.] -- State-owned banks in China / Nicholas R. Lardy -- State -owned banks in Indonesia / P.S. Srinivas and Djauhari Sitorus -- Role of state-owned financial institutions in India: Should the government " do" or "lead"? / Urjit R. Patel -- Lessons from Southern Africa / Lewis Musasike ... [et al.] -- Lessons from Indonesia / Pak Rudjito and Hend rawan Tranggana -- Principles for supervision / Jonathan L. Fiechter an d Paul H. Kupiec -- Lessons from Pakistan / Ishrat Husain -- Lessons fr om Uganda / Louis Kasekende -- Empirical studies / George R.G. Clarke, Robert Cull, and Mary Shirley -- Initial public offerings / Fred E. Hui bers -- Employee stock ownership plans / David M. Binns and Ronald J. G ilbert.
Conference proceedings.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Banks and banking -- Government ownership; Financial institutions -- Government ownership; Privatization; Electronic books